ANALISA KONTROL KV SELEKTOR PADA PESAWAT RONTGEN MERK MEDONICA - Wilson Sinaga; Samser Nababan (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2019)
The Problems About KV Selector Control Analysis on X-Ray Medonica Brands are to find out how the influence of KV on X-Ray planes on Image Quality in KV measurements varies at 50KV, 60KV, and 70KV with 100 mA, and 0.20 s (20 mAs), on FFD 100 cm to the same object that was done in the Radiology Room of the Medan Adventist Hospital.Writing this scientific paper using qualitative descriptive research methods by measuring, collecting data directly on the Medonica brand X-ray machine and comparing the results of good photo films to diagnose patients.Exposure is carried out using a focal height to film (FFD) of 100 cm, 100 mA, 0.20 s. By using a KV variation, the field area is adjusted to the collimator lamp as a good indicator of the irradiation field.From the results that will be obtained later will be obtained a comparison between the 3 (three) CV parameters tested and will get good imaging results and will then be continued in the diagnosis of patients.